Morphological Classification of Extraction Sockets and Clinical Decision Tree for Socket Preservation/Augmentation after Tooth Extraction: a Systematic Review - Gintaras Juodzbalys; Arturas Stumbras; Samir Goyushov; Onurcem Duruel; Tolga Fikret Tözüm (eJournal of Oral Maxillofacial Research)
Objectives: The aim of present study was to review current literature concerning extraction socket classification immediately following tooth extraction and the rationales for socket preservation/augmentation procedures and with reference to it suggest novel clinical decision tree for extraction socket preservation/augmentation in aesthetic and non-aesthetic area.